Community sexual health providers' views on immediate postpartum provision of intrauterine contraception. Issue 2 (1st March 2018) - Cooper, Michelle; Boydell, Nicola; Heller, Rebecca; Cameron, Sharon
Abstract : Background: Increasing access to effective postpartum contraceptive methods can reduce the risk of unintended pregnancy and short inter-birth intervals. The need for an additional postpartum visit can be a barrier to women accessing intrauterine contraception after childbirth. Immediate postpartum intrauterine contraception (PPIUC) provision is known to be safe, but is not routinely available in the UK. Establishing this service requires multidisciplinary support, including from community and maternity stakeholders. The aim of this study was to determine the views of community sexual health providers towards PPIUC implementation. Methods: A questionnaire was distributed to attendees at two UK sexual health conferences. Research questions focused on (1) views on PPIUC (2) perceived role of the sexual health provider in PPIUC service and (3) potential challenges anticipated in providing PPIUC aftercare. Free-text boxes were provided for further comment. Analysis was by a mixed methods approach. Results: A total of 240 questionnaires were distributed with 156 completed (response rate 65%). Some 128 respondents (82%) felt 'positive' towards the PPIUC implementation. Most respondents (67.9%) indicated they would be happy to promote PPIUC and provide thread checks. Perceived challenges in providing PPIUC aftercare included staff time, experience in managing clinical issues, and access to ultrasound. Conclusions: Community sexual health providers were positive towards PPIUC implementation, and perceived their role predominantly in the aftercare of women. Several clinical and practical challenges were identified, some of which differ from those previously expressed by other groups. Stakeholder involvement is key to successful implementation of PPIUC, and wider recognition of potential barriers can assist in developing strategies to overcome these.